Frequency and Diversity of Presentation of Migraine Among School Going Children in Rajshahi City. (KYAMC Journal, 2022)
Background: Most people experience headache at some point in their lifetime. Among them a small proportion suffers from migraine. It is difficult to estimate actual prevalence of headache.Objectives: The aim of our study was to measure frequency of migraine among school going children in Rajshahi city and to evaluate different presentations of migraine.Materials and Methods: This is a population based cross-sectional type of descriptive study in which the survey was conducted among school going children aged 12 -16 years at Rajshahi City from January, 2014 to December, 2015. The diagnostic criteria for migraine defined by International Headache Society (IHS) were used. After taking informed consent purposively collected total 271 migraine patients were enrolled for the proposed study. Screening questionnaire (Questionnaire A) was given to total 2000 students (girls 1000 and boys 1000). A detailed Questionnaire B was distributed to those who had headache.Result: Mean (+SD) age of student of migraine was 13(+1) years, highest proportion (43.54%) of student was between 13 to 15 years of age. Higher frequency of migraine was observed in girls (51.4%) as compared to boys (27.8%). Pulsatile headache is the commonest type of headache. Majority of students reported unilateral headache. 80.4% students reported their headache to aggravated by movement. Associated features were photophobia or phonophobia 63.5%, both 26.6%, nausea 82.7%, vomiting 30.6%. Most students (29.5%) reported sleep disturbance as the aggravating factor of migraine and they reported that their attack is relieved by rest.Conclusion: Early diagnosis and treatment of migraine as well as the education of health workers and families are very important. In our environment the numerical importance of this disease suggests the need to perform further and broader epidemiological studies.KYAMC Journal. 2022;12(04): 237-242